2020
DOI: 10.1140/epjc/s10052-020-08433-6
|View full text |Cite
|
Sign up to set email alerts
|

On quintessence star model and strange star

Abstract: The astronomical observations on the accelerated expansion of the universe generate the possibility that the internal matter of the stars is not only formed by ordinary matter but also by matter with negative pressure. We discuss the existence of stars formed by the coexistence of two types of fluids, one associated to quintessence dark matter described by the radial and tangential pressures $$(P_{rq},P_{tq})$$ ( P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…It is also applicable in alternative gravitational theory models [80,81]. This same geometry allows for the description of models that are differentiated for the type of sources of matter in situations with or without equation of state [74,[76][77][78][79][80][81].…”
Section: Basic Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also applicable in alternative gravitational theory models [80,81]. This same geometry allows for the description of models that are differentiated for the type of sources of matter in situations with or without equation of state [74,[76][77][78][79][80][81].…”
Section: Basic Equationsmentioning
confidence: 99%
“…It is also applicable in alternative gravitational theory models [80,81]. This same geometry allows for the description of models that are differentiated for the type of sources of matter in situations with or without equation of state [74,[76][77][78][79][80][81]. The different models proposed were applied to describe the interior of many stellar objects for which their observational data is known and also it has been shown that the geometry is regular and absent of event horizon, motivated by this, in this report the focus will be centered in the construction of a model, the description of it's behaviour and it's application to determining the possible values of the charge considering some values of the Bag constant inside of the admissible interval of it.…”
Section: Basic Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Objects with a greater compactness than in the case of a perfect fluid, corresponding to the Buchdahl limit [1] u ≡ GM/c 2 R < 4/9, can occur when we have a difference between the radial pressure P r and the tangential pressure P t , known as anisotropy Δ = P t − P r [2], in the presence of electric charge [3][4][5] or when we have both situations. The anisotropy in relation to compact objects has been addressed in the analysis of stars with ordinary matter for an incompressible fluid [6] and with non-constant density [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], in the analysis of bosonic stars [22], in the context of Brans-Dicke gravity [23], in alternative gravitation theories like the f (T) [24], in the consideration of stars with quintessence type matter [25][26][27][28][29] and also in the analysis of hypothetical objects such as gravastars [30]. In the charged case we have models that consider a perfect charged fluid [31][32][33][34][35][36][37] as well as in the case of objects with charged anisotropic fluid [38][39][40][41][42]…”
Section: Introductionmentioning
confidence: 99%
“…Ray et al studied the effect of electric charge in compact stars assuming that the charge distribution is proportional to the mass density and the relativistic hydrostatic equilibrium equation, i.e., the Tolman-Oppenheimer-Volkoff equation, gets modified due to the inclusion of electric charge [27]. The dynamics of cold star models, compact stars, strange stars, and other stellar configurations with the hybrid coupling of strange matter have been the subject of continuous research during the last decade [28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%